Transformações de Miura, Bäcklund e hierarquias integráveis - Lobo, Gabriel Vieira [UNESP] (Universidade Estadual Paulista (Unesp), 2023)
Neste trabalho apresentamos a construção sistemática de hierarquias integráveis através da condição de curvatura nula, garantindo a existência de quantidades conservadas. As hierarquias $A_r$-KdV e $A_r$-mKdV são construídas e suas estruturas algébricas são discutidas. Transformações de Miura e Bäcklund são propostas como transformações de gauge que relacionam as hierarquias $A_r$-KdV e $A_r$-mKdV, com regularidade relacionada à estrutura do kernel de $E^{(1)}$. A invariância sob gauge da condição de curvatura nula é enfatizada, juntamente com o papel central do elemento $E^{(1)}$ na restrição dos fluxos temporais de ambas as hierarquias.

In this work, we present the systematic construction of integrable hierarchies through the condition of zero curvature, ensuring the existence of conserved quantities. The $A_r$-KdV and $A_r$-mKdV hierarchies are constructed, and their algebraic structures are discussed. Miura and Bäcklund transformations are proposed as gauge transformations that relate the $A_r$-KdV and $A_r$-mKdV hierarchies, with regularity related to the structure of the kernel of $E^{(1)}$. The gauge invariance of the zero curvature condition is emphasized, along with the central role of the element $E^{(1)}$ in restricting the time flows of both hierarchies.
Miura and Bäcklund transformations and integrable hierarchies
Keywords: Transformações de Bäcklund; Solitons; Equações diferenciais não-lineares; Equação de Korteweg-de Vries; Invariancia de calibre; Bäcklund transformations; Nonlinear differential equations; Korteweg-de Vries equation; Gauge transformations